ARKETIPE PADA CERPEN PRESIDEN JEBULE KARYA BUDI DARMA DALAM PERSPEKTIF ANTROPOLOGI BUDAYA DAN PSIKOANALISIS - andika hendra mustaqim (Wanastra: Jurnal Bahasa dan Sastra, 2017)
The purpose of this research is to explore archetype in the Presiden Jebule written by Budi Darma through cultural anthropology and psychoanalysis. The research method is content analysis to guide the researcher analyze the short story. The finding of the research are focusing to analysis archetype based on Northop Frye’s theory and Carl J Jung’ theory. Presiden Jebule is focus about the image of a dictator who repress his society and the rhetoric using alliteration for repeating consonant to give some strong messages. Other findings are the dictator actually has bad experiences in the past, and Presiden Jebule becomes an icon to deliver his powerful to his society.